INTERACTION OF SCALABILITY PROCESS WITH ENVIRONMENTAL LIMITATIONS ON MICROALGAE CULTIVATION: LIGHT COLOR AND SALINITY EFFECTS - Nina Juliana Roberta Turnip; Rayke Dhiya F.; Yuelia Salsabilla; Ulil Afni; Lestari Lestari; Deviany Deviany; Andri Sanjaya (BRIN - Badan Riset dan Inovasi Nasional, 2026)
Scaling up the cultivation of Chlorella vulgaris often results in differences in growth performance compared to laboratory-scale cultivation due to increased sensitivity to environmental factors. This study examined the interaction between light color, salinity, and the scale-up process at cultivation volumes of 1, 5, and 10 L using synthetic NaCl media and artificial seawater (ASW). Growth was monitored via optical density measurements. The results indicated that inoculum is a key factor factor influencing the success of scale-up. Cultures transferred during the logarithmic growth phase adapted more quickly and maintained exponential growth, while inoculum from the decline phase showed slower recovery and lower cell density. Red light minimized light stress and promoted higher cell density in both media. Lower salinity promoted faster growth and earlier peak attainment. Changes in dry biomass pigments indicate carotenoid accumulation under high salinity and light stress. The highest biomass yield was achieved when harvested during the logarithmic phase, with ASW medium providing higher productivity. Overall, optimizing inoculum age, light, and salinity is crucial for improving production efficiency during the C. vulgaris scale-up process.